The economic integration of Roman Italy : rural communities in a globalizing world - Haas, Tymon C. A. de, 1979-; Tol, Gijs Willem. (Mnemosyne, Supplements, 2017)
Over the past decades, archaeological field surveys and excavations have greatly enriched our knowledge of the Roman countryside Drawing on such new data, the volume The Economic Integration of Roman Italy , edited by Tymon de Haas and Gijs Tol, presents a series of papers that explore the changes Rome's territorial and economic expansion brought about in the countryside of the Italian peninsula. By drawing on a variety of source materials (e.g. pottery, settlement patterns, environmental data), they shed light on the complexity of rural settlement and economies on the local, regional and supra-regional scales. As such, the volume contributes to a re-assessment of Roman economic history in light of concepts such as globalisation, integration, economic performance and growth.